Perspective: Comparison of end-of-life scenarios of municipal solid waste from viewpoint of life cycle assessment - Mannheim, Viktoria (Frontiers in Built Environment, 2022)
Municipal solid waste management systems use several techniques for municipal solid waste at the end-of-life stage. However, to take the major differences to identify good waste management practices and the optimal actions, more complex comparisons need to be discussed. This perspective article discusses the advances and future directions of the given specific research area from the viewpoint of the author with complex review of professional literature and presentation of other authors’ work. This research work assesses and compares the environmental impacts of two end-of-life scenarios (landfilling and conventional incineration) in the European Unio including the practical life cycle assessment. To find the research answers, eight main environmental impact categories, emissions, and primary energies were analyzed using the GaBi 8.0 software. Based on the results, it can be concluded that in the case of incineration, the emissions and the electricity power credit are higher. These research results can be used to compare waste treatment processes with lower environmental impacts, and these can be applied to perform further research on these processes.